Plasma polychlorinated biphenylsdetection among adults with metabolic syndrome and their association with house characteristics, resident’s behaviourperceived indoor air quality, and dietary consumption at UiTM primary care medicine clinic - Othman, Nafisah (2024)
Polychlorinated biphenyls (PCBs) are Persistent Organic Pollutants (POPs) targeted foelimination by 2028 due to their environmental persistence and health risks. Howevethere is scarce information on the prevalence of PCBs in human plasma, especiallamong the Metabolic Syndrome (MetS) population, which is vulnerable to lifestyle andenvironmental-related health risks. To address this gap, this study examined thprevalence of five highly chlorinated PCB congeners (PCB 153, 180, 194, 206, and 209)in the plasma of adults with MetS and their association with house characteristicresident behaviour, perceived indoor air quality (PIAQ), and dietary consumption. cross-sectional study was conducted among 129 MetS patients at the UiTM PCM cliniPlasma PCB was measured under a national project entitled “Elucidating the Effects oPersistent Organic Pollutant - Polychlorinated Biphenyls Exposure on AtherosclerosDevelopment Among Adults with and without MetS.” House characteristics anresidents’ behaviour were assessed in terms of the general condition of the housventilation methods, cooking practices, and cleaning habits, which consisted of 20 questions that were content validated by an expert panel to ensure accuracy in evaluating PCB exposure factors. The participant’s diet was assessed using a 203-itefood frequency questionnaire, while PIAQ was based on seven subjective factorincluding temperature, odour, and humidity. The association between these factors anplasma PCBs was identified using logistic regression analysis. The study resuindicated that at least one PCB congener was detected in 96% of plasma samples, witPCB 206 being the most prevalent. PIAQ significantly predicted all PCB congenerwith perceived hot temperatures associated with PCB 153 (AOR: 2.7167, 95% C1.2705 – 5.8089) and 194 (AOR: 2.3506, 95% CI: 1.1305 – 4.9423) detectionConversely, perceived cold temperatures show a protective effect against PCB 180 (AOR: 0.2118, 95% CI: 0.0427 – 0.9905) but increase the risk of PCB 209 detectio(AOR: 7.7360, 95% CI: 1.2422 – 48.177), indicating the complex relationship betweeindoor temperature and PCB exposure. Unpleasant odours were associated with highrisks of PCB 194 (AOR: 8.5742, 95% CI: 2.3955 – 30.6899) and 206 (AOR: 3.1129,95% CI: 1.0220 – 7.5797), indicating that sensory perceptions might indicaenvironmental contamination. In terms of house characteristics and resident behaviourbuilding age, fan use, and carpet application were associated with increased PCdetection risks, while weekly mopping reduced them. The study also addresses dietarfactors, identifying fish and dairy consumption were associated with a higher risk oPCB 180 and 206 detections (AOR: 1.0880, 95%CI: 1.0064 – 1.0996) and (AOR1.0065, 95% CI: 1.0009 – 1.0128), respectively, while fruit and vegetable consumptioshows a protective effect (AOR: 0.9982, 95% CI: 0.9968 – 0.999). In conclusion, ththreat of PCBs is still prevalent in the population. These findings underscore the neefor comprehensive strategies to manage PCB exposure, particularly in vulnerablpopulations such as those with MetS, by optimising indoor environmental conditionsenhancing ventilation and cleaning practices, and making informed dietary choices.